Effect of Metallic or Non-Metallic Element Addition on Surface Topography and Mechanical Properties of CrN Coatings - Tatyana Kuznetsova; Vasilina Lapitskaya; Anastasiya Khabarava; Sergei Chizhik; Bogdan Warcholinski; Adam Gilewicz; Aleksander Kuprin; Sergei Aizikovich; Boris Mitrin (Nanomaterials, 2020)
Alteration of the phase composition of a coating and/or its surface topography can be achieved by changing the deposition technology and/or introducing additional elements into the coating. Investigation of the effect of the composition of CrN-based coatings (including AlCrN and CrON) on the microparticle height and volume, as well as the construction of correlations between the friction coefficient at the microscale and the geometry of microparticles, are the goals of this study. We use atomic force microscopy (AFM), which is the most effective method of investigation with nanometer resolution. By revealing the morphology, AFM allows one to determine the diameter of the particles, their heights and volumes and to identify different phases in the studied area by contrasted properties. The evaluation of the distribution of mechanical properties (modulus of elasticity E and microhardness H) on the surfaces of multiphase coatings with microparticles is carried out by using the nanoindentation method. It is found that the roughness decreases with an increase in the Al concentration in AlCrN. For the CrON coatings, the opposite effect is observed. Similar conclusions are valid for the size of the microparticles and their height for both types of coating.